University students' perspectives on water security in Malaysia and its impact on National Development - Abdul Mannan, Mohd Zamri (Universiti Malaysia Sarawak, (UNIMAS), 2022)
Amid the frantic pace of rapid globalization, the water security issue has always been a concern among the people in Malaysia, with the accompanying worries concerning national development. This study emphasized the perspective of university students in Malaysia on the impact of water security on the national development of Malaysia. The view of the university students would be explored concerning the current students who are the future leaders of Malaysia in the next few years. This study provided the plan for Malaysia to tackle the urgency of water security amid the rapid globalization in developing the nation. The study provides the significance of the water security issue concerning its contribution to the success of national development in Malaysia of the Twelve Malaysia Plan (12MP). The Water Sector Transformation 2040 (WST2040) has been included in the 12MP concerning the comprehensive preventive measures prepared by the government to tackle the severe water security issue in Malaysia. The WST 2040 plan was introduced as it sets a strategic direction of ensuring the sustainability of the water sector is set accordingly amid the rapid globalization process of developing Malaysia. The WST 2040 aims to provide the consistency of water supply for every people in Malaysia, improve the water management in managing water supply, and empower people concerning the drivers in the WST 2040. Nevertheless, this study employed qualitative research, substituting the qualitative survey in data collection via Google Form as the primary research instrument considering the qualitative method. Hence, this research is executed to identify the perspective of university students on water scarcity and its impact on national development.